Lake morphological characteristics and climatic factors affect long-term trends of phytoplankton community in the Rotorua Te Arawa lakes, New Zealand during 23 years observation - Wu, Naicheng; Guo, Kun; Suren, Alastair M.; Riis, Tenna (Water research (Oxford), 2023)
•Trend of lake phytoplankton over a 23-year period is examined.•Long-term trends of abiotic and biotic indices are highly lake dependent.•Abiotic factors resulted in more regime shifts than biotic indices.•Effectiveness of intervention is underpinned by lake morphology and climate. Monitoring the long-term dynamics of lake phytoplankton can help understand their natural temporal variability, as well as assess potential impacts of interventions aimed at improving lake ecological condition. However, investigating long-term changes in lake ecosystems has received scant attention. In the present study, we analyzed a long-term dataset of phytoplankton communities collected from 1990 to 2013 from eleven of the 12 Rotorua Te Arawa lakes in New Zealand, to explore their responses to changing abiotic conditions. We used a sequential algorithm to examine the likelihood of regime shifts in abiotic and biotic factors during the study period that could be attributable to lake interventions. Our analysis suggests that lake interventions have improved the abiotic factors, whereas the response of biotic factors was less clear. Total phosphorus levels were implicated in the decline in lake condition, including in two lakes subject to lake interventions, and in four control lakes. Both abiotic and biotic factors showed diverse trends (e.g., increase, decrease or no change), and abiotic factors had more regime shifts than biotic factors. Shifts in biotic indices also displayed time lags to shifts in abiotic factors. Long-term responses of abiotic and biotic factors were also influenced by lake morphological characteristics and climatic variables. This latter finding underscores the importance of considering lake morphological characteristics and climate changes when planning management practices. A sound understanding of resilience and threshold of phytoplankton shifts to environmental changes are needed to assess the effectiveness of previous management strategies and prioritize the future conservation efforts toward water quality goals. [Display omitted]